Management strategies to improve environmental and economic outcomes of sheep farms in Norwegian coastal and fjord areas. 1. Sustainable use of home-grown feed resources and rangeland pastures - Bhatti M.A.; Eik L.O.; Bernués A.; Singh B.R.; Steinheim G.; Adnoy T.; Asheim L.J. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Norway has vast rangeland resources (292 361 km2) with an estimated carrying capacity of nearly four million lambs and sheep – twice the current number. However, an intensive production system has led to concentrate-dependent indoor feeding and poor utilisation of rangelands and homegrown feeds. In coastal and fjord areas, such intensive production systems limit the use of open landscapes for sheep grazing during the winter. It influences the delivery of ecosystem services such as soil fertility, landscape preservation and biodiversity. The importance of developing animal and environment-friendly sheep grazing systems has also been highlighted recently, emphasizing the use of natural resources that cannot be used for more intensive cropping enterprises. Extensive grazing systems are also capable of producing “green” food products that contribute to regulating soil health, water and nutrient cycling, soil carbon sequestration, and recreational environments. These are appreciated by consumers and society at large and may be economically sustainable for farmers. In this paper, the economics of the current sheep feeding practices are compared with a more extensive system allowing for higher intakes of on-farm feed resources using a linear programming model. Changes in the current management practices have the potential to increase lamb meat production and lower mutton production, in addition to improving the year-round supply of fresh meat. The utility of smaller frame size breeds needs to be explored as a means of achieving these goals. These breeds may also supply a market for smaller meat joints and cuts designed for rapid preparation of meals for time-constrained consumers.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)